School physical education political challenge in initial education: The teaching-pedagogical actions developed by the teachers of a private institution (Revista Contexto & Educação, 2023)
The study objective is to analyze how the teachers who work in the initial formation in Physical Education (PE), develop their training actions with the intention of contributing to teachers training who understand school and school PE social responsibilities. Therefore, a qualitative and descriptive research was developed, with eleven teachers participation. The results indicate that the didactic-pedagogical strategies reveal a fragmentary character and are developed with a certain fragility. Thus, it is concluded that, for initial formation teachers, it may be essential to assume the role of teacher of future teachers, which implies thinking beyond the technical, instrumental and methodological subjects sphere in isolation. By not developing a formative process guided by full-fledged theoretical studies and debates and with defined intentions, the potential for training a teacher with the capacity to develop an educational proposal for PE, articulated with the social school responsibilities and the school PE itself is diminished.